The Effectiveness of Beginning Reading and Writing Skills Learning with PWIM and CIRC at The First Grade Students (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Learning in reading and writing is given in elementary school for the first grade Students known as Beginning Reading and Writing (MMP) is a habit for the first grade students to recognize basic literacy. Beginning reading and writing learning are carried out with innovative models that need to be measured for effectiveness. The aims of this tudy is to analyze the effectiveness of the initial reading writing skills learning with the picture word inductive models and cooperative integrated reading and composition models at the first students of SD Unggulan Terpadu Bumi Kartini Jepara. This research was conducted with a randomized pre-test - post-test comparison group design. The test and nontest method collect data. The results showed that the use of inductive picture-word models was more effective than using cooperative integrated reading and composition models. This result is based on the results of the t-test, which shows that the average post-test score of the beginning reading and writing skills with the picture word inductive model is higher than using the cooperative integrated reading and composition model (89.4 > 88) with a significance level < 0.05. The conclusion of the research shows that the picture word inductive model is effective in improving beginning reading and writing skills. The inductive word picture model can help students who have difficulty in initial reading and writing.